Efficient organocatalytic route for asymmetric total synthesis of stagonolide F - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron Letters, 2015)
A stereoselective total synthesis of Stagonolide F (98% ee) is described employing asymmetric alpha-aminooxylation, Jorgensen's asymmetric epoxidation, Brown asymmetric allylation, Steglich esterification and ring closing metathesis as key steps. The use of organocatalytic alpha-aminooxylation and Jorgensen's asymmetric epoxidation of aldehydes for the introduction of chirality makes this approach more attractive. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Aminooxylation; Jorgensens's asymmetric epoxidation; Macrolide; Ring-closing metathesis; Total synthesis